2006
DOI: 10.1103/physreve.74.021901
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical approach to tumor growth

Abstract: Tumor growth has a number of features in common with a physical process known as molecular beam epitaxy. Both growth processes are characterized by the constraint of growth development to the body border, and surface diffusion of cells/particles at the growing edge. However, tumor growth implies an approximate spherical symmetry that makes necessary a geometrical treatment of the growth equations. The basic model was introduced in a former article [C. Escudero, Phys.Rev. E 73, 020902(R) (2006)], and in the pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…In order to construct radial growth equations one may invoke the reparametrization invariance principle [21,22], as has already been done a number of times [10,11,[13][14][15][16]. In the case of white and Gaussian fluctuations, the d-dimensional spherical noise is given by…”
Section: Radial Random Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to construct radial growth equations one may invoke the reparametrization invariance principle [21,22], as has already been done a number of times [10,11,[13][14][15][16]. In the case of white and Gaussian fluctuations, the d-dimensional spherical noise is given by…”
Section: Radial Random Depositionmentioning
confidence: 99%
“…A series of works constitutes an exception to this rule [10][11][12][13][14][15][16], as they proposed a partial differential equation with stochastic terms as a benchmark for analyzing the dynamics of radial interfaces. Because studying this sort of equations is complicated by the nonlinearities implied by reparametrization invariance, a simplified version in which only the substrate growth was considered was introduced in [17].…”
Section: Introductionmentioning
confidence: 99%
“…expression that will be evaluated with the help of a small noise expansion [21]: r(θ, t) = R(t) + √ ǫρ(θ, t), where the noise amplitude ǫ is assumed to be small enough. We get R(t) = F t, for t > t 0 , and…”
mentioning
confidence: 99%
“…However, the long time behavior shows a marked weakening of the fluctuations, and, as we will show, the logarithmic dependence is the footprint of critical dimensionality. The two-dimensional random deposition equation is [21] …”
mentioning
confidence: 99%
“…Subsequent works were devoted to the radial (1 + 1d) KPZ equation [16,17,18], the radial (1 + 1d) and spherical (2 + 1d) Mullins-Herring (MH) equa-tion [19,20], and the general reparametrization invariant formulation of stochastic growth equations [21]. An analytical approach to these equations [18] showed that for short spatial scales and time intervals the dynamics of radial interfaces was equivalent to that of the planar case; however, long time intervals yielded a different output.…”
Section: Introductionmentioning
confidence: 99%